Security models in mega sport events between safety and human rights (case of Vancouver 2010) (The Sport Journal, 2013)
This study examines the conflict between liberty and security in sporting mega-events by ensuring that prohibited items do not enter an Olympic Games venue while guaranteeing service excellence. A random sample of spectators and journalists (N= 1081) from Vancouver 2010 Winter Olympics responded to a survey about customer service and security in the event. Chi-square tests for two independent samples were used along with Crosstabs procedures to test the differences in service and security between journalists and spectators. The results revealed that a successful security model in mega-sport events is based on two pillars: service excellence that depends on the time spent at the portal, the communication with customers, the kind of staff serving in the venue, and mainly on the cooperation between all security corps in charge.